MENDORONG EKONOMI SIRKULAR: PELATIHAN PENGOLAHAN URINE KELINCI MENJADI PUPUK ORGANIK CAIR BAGI MASYARAKAT SEKITAR HUTAN - YOKO, BUDI (Jurnal Abdi Masyarakat Indonesia (JAMIN), 2024)
Farmers living around the forest face various economic vulnerability issues. This community service activity seeks to implement circular economy practices through training in producing liquid organic fertilizer using rabbit urine as a raw material. This initiative encourages communities to utilize waste from rabbit husbandry activities to create economically valuable products. Through a participatory approach, the community enthusiastically participates in these activities. Based on the results of the analysis, this training effectively enhances the community's knowledge regarding the production of liquid organic fertilizer from rabbit urine. The sustainable implementation of this initiative is expected to provide additional economic benefits to the community while addressing environmental issues arising from unused rabbit husbandry waste. Moreover, applying liquid organic fertilizer derived from rabbit urine on crops cultivated by farmers represents an initial step towards practicing sustainable integrated farming concepts.